Integration of Email and Task Lists - Corston-Oliver, Simon H.; Ringger, Eric; Gamon, Michael; Campbell, Richard (American Association for Artificial Intelligence, 2004)
Email has evolved from a mere communication system to a general tool for organizing workflow. Widely used email clients address this issue by providing additional functionality, including contact management, calendaring and task lists (i.e., “to do” lists). However, some of these functions are poorly integrated. For example, to create a task, a user might have to switch from an email view to manually fill in a form. We describe SmartMail, a system that improves the integration of the various functions of an email client by identifying the speech act of each sentence in an email message and performing actions appropriate to the speech act. We consider fifteen application-specific speech acts, but our focus to date has been the processing of tasks; SmartMail helps users prioritize emails by identifying tasks.